Evaluation of Efficacy & Biochemical Effects of Pharmaceutical Optimized Amlodipine 5mg (F-5) with Essential Hypertension (Medical Forum Monthly, 2024)
Introduction: An adequate blood pressure is a treatment of hypertension and it is the risk of cardiovascular morbidity and mortality so proper therapy is essential. And the reduction of blood pressure lower than 130/85 mmHg provides additional benefits regarding both protection of organs and cardiovascular mortality. Amlodipine is a calcium channel-blocking agent with vasodilator activity without side effects.Objective: This study aimed to evaluate the efficacy and safety profiles of once-daily optimized amlodipine 5mg (F-5) versus placebo.Study Design: Multicenter, randomized, placebo-controlled, comparative studyPlace and Duration of Study: This study was conducted at the Department of Biochemistry, University of Karachi from April 2011 to September 2011.Materials and Methods: This was multicenter, randomized, placebo-controlled, comparative study. Patients were randomized to receive optimized Amlodipine 5mg (F-5) once daily and Placebo once daily for 8 weeks. The primary efficacy variable was change from baseline in MSDP at the end of study. Secondary variable was change in mean sitting systolic blood pressure from baseline. Biochemical effects were evaluated at the end of study from baseline.Results :In the patients treated with optimized Amlodipine 5mg (F-5) alone, blood pressure reduction was lower, although significant, reaching values of 138.2 ± 10.9 / 88.4 ± 6.5 mmHg (p < 0.05 versus Placebo) by the end of eight weeks of treatment. No significant variations of blood glucose and different parameters of lipid profile were observed during the eight-week of treatment. Thus, the drug regimen used may be considered neutral as regards glucose, plasma lipid metabolism.Conclusion: We can suggest that the high antihypertensive efficacy, good tolerability and no biochemical effects of the optimized Amlodipine 5mg (F-5) it is an excellent option for the treatment of hypertension in a wide range of hypertensive patients, with a high potential to reduce cardiovascular risks.